Comparative Analysis of the Efficacy and Safety of Different Traditional Chinese Medicine Injections in the Treatment of Cancer-Related Pain: A Bayesian Network Meta-Analysis - Su, Pengli; Leng, Yuanyuan; Liu, Jun; Yu, Yanan; Wang, Zhong; Dang, Haixia (Frontiers in Pharmacology, 2022)
Background: Given the limitations of three-step analgesic therapy and the extensive use of traditional Chinese medicine injections (TCMIs) for cancer-related pain (CRP), this network meta-analysis (NMA) aims to compare the efficacy and safety of different regimens of TCMIs for CRP. Methods: A literature search was conducted in seven electronic databases for all related articles published before 12 April 2021. Randomized controlled trials (RCTs) were screened by a prior eligible criteria. The quality of literature was evaluated by the Cochrane risk of bias tool. We used Stata 16.0 software to analyze data including total pain relief rate, quality of life, and the incidence of adverse reactions. The surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the interventions. Radar map was used to exhibit the most outstanding regimen for a certain outcome. Synthetic sorting bubble diagram was performed to show the relatively better regimen by integrating two or three outcomes. Results: A total of 84 RCTs involving 8,044 patients were included. The results indicated that YDZYR + AN (Yadanziyouru injection plus analgesic) ranked first for pain relief rate, closely followed by KLT + AN (Kanglaite injection plus analgesic). AD + AN (Aidi injection plus analgesic) ranked first for quality of life, KLT + AN following closely. The total adverse reaction rate of FFKS + AN (Fufangkushen injection plus analgesic) was the lowest, and the constipation rate of FFKS was the lowest. In terms of the incidence of nausea and vomiting, KLT + AN was the best choice. In the plots analysis, the results of integrated total incidence of adverse reactions and pain relief rate analysis indicated that FFKS + AN was the most appropriate regimen. Meanwhile, it had the lowest incidence of integrated constipation, nausea and vomiting, and total adverse reactions. KLT + AN was the best in alleviating pain and improving quality of life integrated outcomes. Conclusion: In conclusion, FFKS + AN was the best treatment regimen for the pain relief rate and total adverse reaction rate, and it was also the safest regimen for CRP treatment. KLT + AN was the most effective choice. Further, compared with analgesic treatment alone for patients with CRP, TCMIs + AN combination treatment strategies are significantly more effective. However, more high-quality RCTs are required to support these conclusions. Systematic Review Registration: (https://www.crd.york.ac.uk/prospero/#recordDetails, https://www.crd.york.ac.uk/prospero/export_details_pdf.php), identifier (ChiCTR-ONC-CRD42021267829)